The role of dietary fiber in functional nutrition - A. M. Solomon (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького. Серія: Харчові технології, 2024)
The process of nutrition is a function of the relationship between a person and the environment. Food should contribute to the adaptation of the human body to unfavorable conditions and, in addition to its main function – meeting the physiological needs of the human body for nutrients and energy, also perform preventive and therapeutic tasks. Recently, the popularity of healthy food has increased. Experts predict that the market for functional products is growing every year. In this regard, in many countries, in-depth research is being carried out on the structure, composition, properties of dietary fiber, and the technology of their use as one of the components in the creation of composite food products. Dietary fiber is a large group of polymeric substances of different chemical nature, the sources of which are plant products. The composition of nutrients with a fibrous structure includes large quantities of second-order polysaccharides. Dietary fiber is an active participant in the digestive process, a source of essential nutrients; its deficiency or absence can lead to disruption of homeostasis, the dynamic constancy of the internal environment of the body and pathology. Dietary fiber plays an important role in the functioning of a number of organs and systems of the body and, first of all, affects the function of the colon. They adsorb significant amounts of bile acids, as well as other metabolites, toxins and electrolytes, which helps detoxify the body. For a long time, dietary fiber was considered unnecessary ballast, from which attempts were made to free products to increase their nutritional value. In this regard, a number of refined products have been developed that are completely free of ballast substances. Dietary fiber plays an extremely important role in the functioning of the colon. One of their main properties is the ability to retain water. Water-soluble dietary fibers contained in vegetables and fruits are the most hygroscopic. The ability of dietary fiber to retain water accelerates intestinal transit and peristalsis of the colon, changes intraintestinal pressure, and the concentration of fecal electrolytes. One aspect of the physiological effect of dietary fiber is its effect on mineral metabolism. There is evidence that high dietary fiber intake may disrupt the body's mineral balance. These processes are based on the metabolic properties of ballast substances, which promotes the removal of heavy metal ions, such as lead, strontium, and allows us to consider the possibility of using fiber to remove radionuclides from the body. The use of plant additives from cereals in the development of fermented milk products is of scientific interest and is one of the current trends in the development of functional nutrition products.